2016
DOI: 10.1155/2016/3414319
|View full text |Cite
|
Sign up to set email alerts
|

The Effects ofAgave fourcroydesPowder as a Dietary Supplement on Growth Performance, Gut Morphology, Concentration of IgG, and Hematology Parameters in Broiler Rabbits

Abstract: This study was conducted to determine the effects of Agave fourcroydes powder as a dietary supplement on the growth performance, gut morphology, serum concentration of IgG, and the hematology parameters of broiler rabbits. A total of 32 rabbits [New Zealand × Californian] were weaned at 35 days. They were randomly selected for two dietary treatments (eight repetitions per treatment), which consisted of a basal diet and a basal diet supplemented with 1.5% dried-stem powder of A. fourcroydes. On day 60 from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
4
16
0
Order By: Relevance
“…The use of these marine bioactive appears to have the same effect on the BW of growing (Table 2) and adult birds (Kulshreshtha et al, 2014). It is known that prebiotics stimulate the growth of bacterial species and improve host health, especially intestinal health (Iser et al, 2016), however, some studies in birds with these non-digestible products found no benefits in…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of these marine bioactive appears to have the same effect on the BW of growing (Table 2) and adult birds (Kulshreshtha et al, 2014). It is known that prebiotics stimulate the growth of bacterial species and improve host health, especially intestinal health (Iser et al, 2016), however, some studies in birds with these non-digestible products found no benefits in…”
Section: Resultsmentioning
confidence: 99%
“…eRBCA-2019-1015 body weight (Torres-Rodriguez et al, 2005;, it seems that growth promotion must be combined with other beneficial chemical compounds (Iser et al, 2016).…”
Section: Effects Of Dietary Supplementation With Red Algae Powder (Chmentioning
confidence: 99%
“…Although it was observed that T1 increased numerically the AMEn, maybe a higher concentration of this mixed powder of medicinal plant leaves may be necessary to modify these indicators in broilers. e level of serum antibodies is currently an important indicator to know the effect of a new natural product on immune response in experimental animals [27]. An increased immunoglobulin concentration has been associated with a benefit in the immune status, and IgG and IgA are the main Journal of Chemistry immunoglobulins protecting against pathogenic microorganisms [28], mainly to intestinal level.…”
Section: Discussionmentioning
confidence: 99%
“…Morphometric analysis was performed by Image®-Pro Plus software. The evaluated morphometric indices were: villus height (Vh, from the villous tip to the crypt bottom), crypt depth (Cd, from the crypt bottom to the submucosa) and the villus height to crypt depth ratio (Vh/Cd; Additional file 1) [34, 35]. Morphometric measurements were performed on 10 well-oriented and intact villi and 10 crypts chosen from each gut segment.…”
Section: Methodsmentioning
confidence: 99%